2021
DOI: 10.1038/s41598-020-80956-0
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of the eukaryotic dolichol-linked oligosaccharide scramblase suggested by activity correlation profiling mass spectrometry

Abstract: The oligosaccharide required for asparagine (N)-linked glycosylation of proteins in the endoplasmic reticulum (ER) is donated by the glycolipid Glc3Man9GlcNAc2-PP-dolichol. Remarkably, whereas glycosylation occurs in the ER lumen, the initial steps of Glc3Man9GlcNAc2-PP-dolichol synthesis generate the lipid intermediate Man5GlcNAc2-PP-dolichol (M5-DLO) on the cytoplasmic side of the ER. Glycolipid assembly is completed only after M5-DLO is translocated to the luminal side. The membrane protein (M5-DLO scrambla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 67 publications
2
13
0
Order By: Relevance
“…Parental cells (SmOx P9) showed a strong radiolabeled GPEET band, as well as a weak band corresponding to EP procyclin ( Fig. 3 A ), and as expected ( 41 ), no labeled procyclins were detected in a control sample of T. brucei procyclic forms that lack TbGPI13, the enzyme that adds phosphoethanolamine to the third mannose of the GPI anchor. Interestingly, TbGPI2-KO cells showed a radiolabeled band with a lower apparent mass than GPEET procyclin in parental cells.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Parental cells (SmOx P9) showed a strong radiolabeled GPEET band, as well as a weak band corresponding to EP procyclin ( Fig. 3 A ), and as expected ( 41 ), no labeled procyclins were detected in a control sample of T. brucei procyclic forms that lack TbGPI13, the enzyme that adds phosphoethanolamine to the third mannose of the GPI anchor. Interestingly, TbGPI2-KO cells showed a radiolabeled band with a lower apparent mass than GPEET procyclin in parental cells.…”
Section: Resultssupporting
confidence: 79%
“…1 A ). Slower growth of GPI-deficient procyclic cells has been reported previously in some instances, for example, after knocking out TbGPI13 or TbGPI10 ( 24 , 41 ), but not TbGPI12 ( 25 ). Growth was restored by expressing an ectopic copy of TbGPI2 (TbGPI2-HA, bearing a C-terminal 3x HA tag) in the TbGPI2-KO parasites ( Fig.…”
Section: Resultssupporting
confidence: 67%
“…A GlcNAc and five Man residues then are sequentially added from UDP‐GlcNAc and GDP‐Man by the successive actions of multi‐enzymatic complexes ALG13/14 and the three mannosyltransferases ALG1 (β(1,4)‐mannosyltransferase), ALG2 (α(1,3)/(1,6)‐mannosyltransferase) and ALG11 (α(1,2)‐mannosyltransferase) (Gao, Nishikawa & Dean, 2004 ) to yield the dolichol pyrophosphate heptasaccharide Man 5 GlcNAc 2 ‐P‐P‐Dol. At this stage, the LLO undergoes a trans bilayer translocation across the ER membrane, requiring the activity of a flippase (Alaimo et al ., 2006 ; Rush, 2016 ; Verchère et al ., 2021 ). In humans, deficiency of the proposed flippase RFT1 leads to a severe decrease in N ‐glycosylation site occupancy on newly synthesized glycoproteins (Vleugels et al ., 2009 ).…”
Section: N ‐Glycan Biosynthesis In the Er: A Conserved Proce...mentioning
confidence: 99%
“…However, these molecules have at least 12-14 sugar moieties, so given their size, it is unlikely that a single transporter could catalyze their flipping. Later studies refuted the scramblase concept and suggested instead that RFT1 could serve as an accessory protein to a flippase, but would not act as a flippase itself [107][108][109].…”
Section: Othersmentioning
confidence: 99%